Health comorbidities and cognition in 1948 patients with idiopathic Parkinson’s disease - Jones, J.D. (Parkinsonism Relat Disord, 2012)
BACKGROUND: Health comorbidities, particularly cardiovascular factors, are well known to pose risks for cognitive decline in older adults. This study examined the prevalence and contribution of comorbidities on cognitive performance in a large cohort of Parkinson patients. METHODS: Data on 1948 PD patients were obtained from the National Parkinson Foundation Quality Improvement Initiative (NPF-QII) registry, a multi-site initiative from NPF Centers of Excellence. Available comorbidity data included six common conditions (heart/circulation problems, diabetes, arthritis, cancer, respiratory disease, and other neurologic disease) that were clinician-rated for presence and severity. Available cognitive measures included semantic fluency and a 5-word recall memory task. The unique effects of comorbidities on cognition were analyzed (multiple hierarchical regression) controlling for demographic, PD disease severity (duration, Hoehn-Yahr), and medication status. RESULTS: The two most reported comorbidities were arthritis (46.6%) and heart/circulation problems (36.3%), with diabetes affecting 9% of the sample. Severity of heart/circulation problems independently contributed to worse delayed recall performance (p = 0.03). A trend emerged for more severe diabetes as contributing to worse semantic fluency scores (p = 0.06). CONCLUSIONS: This study with a large cohort of PD patients provides evidence for a small detrimental influence of specific health comorbidities, particularly heart/circulatory and diabetes, on general measures of cognition. This effect is present, above and beyond the influences of basic demographic information (age), duration and staging of PD, and medication status. Future studies involving more refined cognitive indices and direct assessment of comorbidities are warranted.